A new apterous genus of Carventinae (Hemiptera: Aradidae) from China - Cui, Jianxin; Bai, Xiaoshuan; Heiss, Ernst; Cai, Wanzhi (Zootaxa, 2015)
A new apterous aradid, Paramorphocoris henanensis Bai & Heiss Cai, gen. et sp. nov., from China is described and illustrated, including the diagnostic morphological features of the new taxon.